2021
DOI: 10.1038/s42003-021-02298-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-mediated induction of caveolin-1 disrupts cytoskeletal organization, inhibits cell migration and re-epithelialization of non-healing wounds

Abstract: Although impaired keratinocyte migration is a recognized hallmark of chronic wounds, the molecular mechanisms underpinning impaired cell movement are poorly understood. Here, we demonstrate that both diabetic foot ulcers (DFUs) and venous leg ulcers (VLUs) exhibit global deregulation of cytoskeletal organization in genomic comparison to normal skin and acute wounds. Interestingly, we found that DFUs and VLUs exhibited downregulation of ArhGAP35, which serves both as an inactivator of RhoA and as a glucocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
3
19
0
Order By: Relevance
“…The GO enrichment analysis performed in the present study was consistent with a number of previous studies showing that the wound healing process of diabetic ulcers is associated with altered extracellular matrix deposition ( 20 ), cytoskeletal deregulation ( 21 ), dyslipidemia ( 22 ) and prolonged inflammation response ( 23 ). The present study unexpectedly found some signaling pathways that seemed weakly relevant to the curative effect of wounds in the enrichment analysis of KEGG signaling pathways, such as thyroid hormone synthesis, thyroid hormone signaling pathway, human T-cell leukemia virus 1 infection and African trypanosomiasis.…”
Section: Discussionsupporting
confidence: 91%
“…The GO enrichment analysis performed in the present study was consistent with a number of previous studies showing that the wound healing process of diabetic ulcers is associated with altered extracellular matrix deposition ( 20 ), cytoskeletal deregulation ( 21 ), dyslipidemia ( 22 ) and prolonged inflammation response ( 23 ). The present study unexpectedly found some signaling pathways that seemed weakly relevant to the curative effect of wounds in the enrichment analysis of KEGG signaling pathways, such as thyroid hormone synthesis, thyroid hormone signaling pathway, human T-cell leukemia virus 1 infection and African trypanosomiasis.…”
Section: Discussionsupporting
confidence: 91%
“…If the proposed role for caveolins in FFA pathogenesis ( Jozic et al., 2021b ) is confirmed, this warrants investigation whether topical perturbation of intrafollicular CAV1, either pharmacologically (e.g., through cyclodextrins/statins) ( Jozic et al., 2021a , 2019 ; Sawaya et al., 2019 ) or by nanoparticle-mediated small interfering RNA delivery, can halt the—often relentless—progression of FFA/LPP and can be used as an auxiliary therapy to the other candidate therapeutics discussed in this paper. Interestingly, the OR2AT4 agonist, Sandalore, which prolongs anagen ex vivo ( Chéret et al., 2018 ), also downregulates the expression of CAV1 at both mRNA and protein levels ( Chéret et al., 2020 ; Jozic et al., 2021b ).…”
Section: Future Directions and Therapeutic Interventionsmentioning
confidence: 98%
“…We identified a mechanism of miR193b-3p antimigratory activity via the disruption of stress fiber formation, the actin structures fundamental for cell motility ( 62 , 63 ). Activation of small GTPase RhoA directly leads to stress fiber formation ( 64 ).…”
Section: Discussionmentioning
confidence: 99%